THE EXTRACTION OF TUNA FISH SKIN(Thunnus albacares) INTO GELATINWITH DIFFERENT OF SULFURIC ACID CONCENTRATIONS - Suhardiyanto Suhardiyanto; Mery Sukmiwati; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study was aimed to get the best concentration of sulfuric acid to extraction of tuna fish skin into gelatin. The raw material of skin tuna was obtained from PT. Dempo Andalas Samudera Bungus Padang City of West Sumatra Province. The method used was an experimental method with Completely Randomized Design (CRD) non factorial consisting of 3 treatment levels, namely the addition of different concentration of sulfuric acid G1 (2% sulfuric acid), G2 (4% of sulfuric acid) and G3 (6% of sulfuric acid). The data was analyzed with ANAVA. The parameters measured in this study were yield, acidity (pH), moisture content, ash content, viscosity and gel strength. The results showed that the tuna fish skin extraction process with 6% sulfuric acid concentration (G3) was the best treatment with a yield value 5.62%, acidity (pH) 3.97, moisture content 5.68%, ash content 4.57 %, viscosity 4.92 cP and gel strength 324.22 g bloom. Keywords: extraction, gelatin, Sulfuric acid,Tuna fish skin